Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1007/bf00011361
|View full text |Cite
|
Sign up to set email alerts
|

The K/Na and Ca/Na ratios and rapeseed yield, under soil salinity or sodicity

Abstract: Rapeseed (Brassica napus) is a crop relatively tolerant to salt and sodium. Our objective was to study the interactions between Na, K and Ca and their relationship with its yield under the isolated effects of soil salinity or sodicity.Two experiments were carried out using pots filled with the Ah horizon of a Typic Natraquoll. There were three salinity levels (2.3 dS m-1; 6.0 dS m-1 and 10.0 dS m-1) and three sodicity levels, expressed as sodium adsorption ratios (SAR: 12; 27 and 44). The soil was kept near fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
4
30
0
1
Order By: Relevance
“…The K/Na and Ca/Na ratios are indicative for soil salinity (Porcelli et al 1995). In the present study, these ratios were the highest at control sites (Fig.…”
Section: Elements Transfer From Soil To Plantssupporting
confidence: 57%
“…The K/Na and Ca/Na ratios are indicative for soil salinity (Porcelli et al 1995). In the present study, these ratios were the highest at control sites (Fig.…”
Section: Elements Transfer From Soil To Plantssupporting
confidence: 57%
“…Indeed, the salt-including habit of many species in this family has been documented as early as 1896 (von Marilaun 1896). In more recent times, He and Cramer (1993) investigated K + /Na + ratios in shoot tissue of six Brassica species, near relatives of Arabidopsis, and found that they bore no relation to salt tolerance, while Porcelli et al (1995) showed that yields and shoot growth of Brassica napus plants were not correlated with tissue K + /Na + or Ca 2+ /Na + ratios.…”
Section: Sodium Toxicitymentioning
confidence: 99%
“…Salinity impairs the uptake of Ca by plants, possibly by displacing it from the cell membrane or in some way affecting membrane functions (Rameeh et al, 2004;Mandhania et al, 2010). Gorham (1993) claimed that all plants discriminate to some extent between Na and K. Na can be substituted for K for uptake, and it is supposed that similar mechanisms of uptake may operate for both ions (Tie and Cramer, 1992;Porcelli et al, 1995;Schroder et al, 1994). High level of K in young expanding tissue is related to salt tolerance in many plant species (Ashaf and McNeilly, 2004;Bandeh-Hagh et al, 2008;Mer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%